2011
DOI: 10.3233/jvr-2011-0544
|View full text |Cite
|
Sign up to set email alerts
|

Predicting vocational rehabilitation outcomes of young adults with specific learning disabilities: Transitioning from school to work

Abstract: Individuals with specific learning disabilities are a heterogeneous group with varied academic challenges and cognitive processing challenges. The manifestations of specific learning disabilities interfere with the acquisition of academic skills and impede vocational success. This study analyzed the Rehabilitation Services Administration (RSA) case service report (RSA-911) data for fiscal year (FY) 2007 to examine effects of demographic characteristics and employment outcomes of persons with specific learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
(30 reference statements)
1
9
1
Order By: Relevance
“…At ap pli ca tion for VR ser vices there were high lev els of hav ing less than a high school ed u ca tion for all youth in this study. The rates of hav ing less than a high school ed u ca tion for par tic i pants in this study were higher than has been reported pre vi ously for youth with LD (Gon za lez et al, 2011;Thurlow, 2012). White youth had the high est rates of less than a high school ed u ca tion, with Af ri can Amer i can youth hav ing rates be tween White and His panic youth.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…At ap pli ca tion for VR ser vices there were high lev els of hav ing less than a high school ed u ca tion for all youth in this study. The rates of hav ing less than a high school ed u ca tion for par tic i pants in this study were higher than has been reported pre vi ously for youth with LD (Gon za lez et al, 2011;Thurlow, 2012). White youth had the high est rates of less than a high school ed u ca tion, with Af ri can Amer i can youth hav ing rates be tween White and His panic youth.…”
Section: Discussioncontrasting
confidence: 65%
“…Re cent re search has in di cated a drop out rate of 14.7% for youth with LD (Thurlow, 2012). How ever, drop out rates have been re ported as high as 58.5% for youth with LD who re ceived vo ca tional re ha bil i ta tion (VR) services (Gonzalez, Rosenthal, & Kim, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nationally, 44% of transitionage SSA beneficiaries who applied for and received VR services were employed at the time of case closure. In comparison, nationally, of all non-SSA VR youth who 2004-2011ACS 2004ACS -2006DAF. N = 413,285.…”
Section: Tomentioning
confidence: 99%
“…Additionally, 56% of people with SLD and co-occurring intellectual disabilities obtained competitive employment after receiving VR services (Dunham et al, 2000). More recently, Gonzalez et al (2011) revealed that 62.4% of youth with SLD obtained competitive employment after receiving VR services. Most of the VR services for individuals with SLD were on-the-job training, job coaching, and counseling services (Dunham et al, 2000).…”
Section: Introductionmentioning
confidence: 99%